(untitled) (Research, Society and Development, 2021)
Objective: analyzing the dreams of preceptors that could be implemented, to contribute to the strengthening of a Multiprofessional Residency Program in Health (RPH). Method: Our article is a Critical Appreciative Study with Permanent Health Education (PHE) as theoretical orientation and its concepts linked to the critical social theorist Paulo Freire. This research was developed with seven preceptors of the Multiprofessional Integrated Residency Program of the Clinical Hospital of Porto Alegre. Data were obtained in interviews and discussion groups through a DSPD cycle: Discovery, Dream, Planning and Destiny, after approval by the Ethics and Research Committee. Results: relating to the dreams of the preceptors, we highlight that these are directed to the valorization of preceptors, to the use of the resident as a human resource for the Unified Health System (SUS), to the investment and qualification of the pedagogical structure of residency programs and expansion of the resident’s training camps. In addition, dreams that can be feasible through initiative or the intervention of preceptors, how to stimulate interprofessional exchanges and between the different emphasis within the same program, or between different residency programs, were identified. Conclusion: We observed that the preceptors brought important reflections about their practices in their workspace in a dialogical, reflexive and participatory process, in favor of advances in RPH and consequent qualification of health care to SUS users.